Radiography of a structure. Eduardo Torroja and the San Carlos Clinical Hospital of Madrid - Lorente de Diego, Alba; Martín-Gómez, César; Castro Molina, Francisco Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
The structure tends to go unnoticed, being found under the floors, behind the walls, but it has the capacity to release or restrict the architectural project. The development of reinforced concrete was a fundamental change in the development of new structures, generating new architectural typologies and providing flexibility to the new constructions of the 20th century. The hospital typology of this century is a model when it comes to demonstrating the importance of the structure within the architectural project. It is an architectural type that hold inside them a wide variety of activities, and where the technical development plays a decisive role. Therefore, the structure appears in some examples as in the case of the San Carlos Clinical Hospital of Madrid, designed by Eduardo Torroja and Manuel Sánchez Arcas, as generator of a continuous rhythm, of a base, where to fit the variability of the spaces and give rise to a multidisciplinary building capable of transforming and remaining over time. Thus, the object of study of this article is to explain justifiably how this structure has allowed the continued use over more than 80 years of this building, despite the permanent changes required by a construction of these characteristics.